Case of acquired idiopathic cold‐induced hyperhidrosis. Issue 3 (29th May 2013) - Tsuge, Ayako; Kaneko, Satoshi; Wate, Reika; Yamazaki, Fumikazu; Kusaka, Hirofumi
Abstract We report the case of a 76‐year‐old man with a 10‐year history of cold‐induced sweating. He noticed excessive sweating in winter starting at the age of 66 years. The sweat appeared shortly after exposure to a cold environment, and was limited to his neck, chest and arms. Piloerection was also noticed in the sweating areas. The results from a heat‐induced sweating test and axon reflex sweating test, as well as the histology of his sweat glands, were normal. The heart/mediastinum ratio of 123I‐metaiodobenzylguanidine uptake was reduced, suggesting underlying pathomechanisms of incidental Lewy body disease. The cold‐induced sweating and elevation of plasma noradrenaline were inhibited by clonidine and amitriptyline. These results suggest the possibility of misconnection of afferent inputs under a cold environment to efferent pathways of heat‐induced sweating.